ANALISIS KELAYAKAN RUTE PENERBANGAN JOGJAKARTA-BANJARMASIN-JOGJAKARTA DENGAN PESAWAT B-737 SERI 200 - Rahimudin, Rahimudin (Fakultas Ekonomi dan Bisnis Universitas Ahmad Dahlan, 2013)
Yogyakarta-Banjarmasin-Yogyakarta was very potential route for airlines to select as their planning route selection because of demand of both city has growth significantly. This new route selection becomes very important as research material because it can determine a companys cost advantage in taking the existing market potential. Until now, only Lion Air has established with this route and gets the profit significantly. The aims of this case study was to determine the feasibility of these airlines Yogyakarta-Banjarmasin-Yogyakarta based on analysis of airport operations, demand of passenger in both sectors and also analyze operational costs by using the model of demand of passenger aircraft Yogyakarta-Banjarmasin-Yogyakarta. Passenger demand equation model is determined by analyzing the historical data of passenger demand Yogyakarta-Banjarmasin-Yogyakarta through multiple linear regression method. Equation model was developed to estimate the number of annual passenger demand Yogyakarta-Banjarmasin-Yogyakarta as independent variables and the dependent variable is the total number of passengers in Yogyakarta-Banjarmasin-Yogyakarta, PDRB (Product Domestics Regional Brutto) and also income per capita.